(untitled) - Sawasawa, Wilson (Can Tho, 2020)
Channa lucius is one of endangered and economically important species in Channidae family with high potential for aquaculture in the Mekong Delta. However, limited genetic information has obstructed the conservation and domestication programs of this species. The present study employed Inter-Simple Sequence Repeats (ISSR) markers to assess genetic diversity of C. lucius. Samples were collected from three conservation locations (Ca Mau, Kien Giang and Long An) and one from inland fisheries areas (Can Tho) in the Mekong Delta. Eight highly polymorphic markers yielded 76 scorable bands from 93 samples (22 to 24 samples per population) with the size range from 450 to 2000 bp. Results revealed high levels of genetic diversity of C. lucius populations with unbiased expected heterozygosity from 0.250 to 0.271 and Shannon index from 0.364 to 0.395, in which those of Ca Mau population were lowest. Nei’s genetic distance between populations ranged from 0.022 to 0.057 with low overall genetic difference Gꜱт = 0.090 and high gene flow (Nm = 5.06), indicating that C. lucius populations were not subdivided. This study provided useful information for conservation projects for this species in the region.
Keywords: Aquaculture,Nuôi trồng thủy sản